2018
DOI: 10.1016/j.ygyno.2018.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Processing of fallopian tube, ovary, and endometrial surgical pathology specimens: A survey of U.S. laboratory practices

Abstract: Changes in the theories of pathogenesis of high-grade serous carcinoma have led to implementation of pathology specimen processing protocols that include detailed analysis of the fallopian tubes. These results have implications for interpreting trends in cancer incidence data and considering the feasibility of developing a bank of gynecologic tissues containing STIC or early cancer precursors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Although criteria for diagnosing STIC have been proposed, there is still significant interobserver disagreement. 6 In certain scenarios, frequency of STIC is difficult to determine, like in cases of metastases involving fallopian tube and mimicking STIC, interobserver variability, sampling or effacement of fallopian tube by large carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…Although criteria for diagnosing STIC have been proposed, there is still significant interobserver disagreement. 6 In certain scenarios, frequency of STIC is difficult to determine, like in cases of metastases involving fallopian tube and mimicking STIC, interobserver variability, sampling or effacement of fallopian tube by large carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…The paper states there is minimal evidence-based data that evaluate the health outcomes related to exempt status or gross only examination policies for specific specimens. Furthermore, institutions that performed more surgeries were found to have more exempt status tissues while teaching hospitals had less exempt status tissues in this study [2,6]. This may indicate that the medical benefit of pathologic examinations is overstated seeing as institutions with a higher caseload more often forgo the exam.…”
Section: Discussionmentioning
confidence: 77%
“…With the evidence presented in this review, the incidence of STIC has been reported in less than 1% of specimens removed for benign indications [6] and HGSC rates are low according to population risk. In one series of 522 average-risk women undergoing salpingectomy, only four cases were detected [12].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The modified and full serial examination and embedding of the fimbriae (SEE-FIM) methods more comprehensively examine the fimbriated end of the fallopian tubes than the examination of one random section of the distal end (14). SEE-FIM increases the detection of serous tubal intraepithelial carcinoma (STIC) and early tubal serous carcinoma (15,16).…”
mentioning
confidence: 99%